Study of the Corrosion Characteristics of Tunnel Fissures in a Karst Area in Southwest China. (24th July 2018) - Zhao, Yanjie; Wang, Fugang; Li, Cangsong; Cao, Yuqing; Tian, Hailong
Abstract : The development of the fissures in soluble rock of karst areas directly affects the construction and operation safety of tunnel engineering. It is thus of theoretical and practical significance to study the characteristics of its corrosion and its influencing factors. Taking the Wulong tunnel as the research object, the numerical model of the study area was established to quantitatively analyze the corrosion range, corrosion ratio, and changes in the permeability and porosity of the fissures in soluble rock of karst areas of the tunnel over the past 100 years, and the simulation results were verified by field experiments. The results show that the main controlling factor of the fissure corrosion of the tunnel in the karst area is the flow rate. The corrosion range and corrosion ratio of the fissures of the tunnels in the karst area increased with temperature because the reaction rate constant increased with temperature, causing the reactions' equilibrium to move towards the direction of the solution. The larger the initial permeability and the larger the porosity of the fissures, the faster the fissures corrode. In the same time period, the fissures with high permeability and large porosity will lead to the permeability and porosity being more enhanced, thus causing the corrosion of the fissures to exhibit secondary enhancement effects. The opening of the dead-end pores greatly enhanced the permeability and slightly increased the porosity, which caused the differential corrosion of fissures in the karst area. The protection of the tunnel should be strengthened, mainly in strong hydrodynamic conditions and in the fracture development zone.